2015
DOI: 10.1016/j.jobaz.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and immunological changes induced by magnetite nanoparticles in the spleen, liver and genital tract of mice following intravaginal instillation

Abstract: Recently, vaccination against sexually transmitted diseases as well as tumor therapy using new systems such as nanomaterials is a promising strategy. For successful usefulness of magnetite nanoparticles (MNPs) in medical applications through the vaginal route, it is essential to understand their biological fate and cellular toxicity in the animal tissues. This study aims to investigate the biodistribution, histopathological and immunological impacts of MNPs on in the liver, spleen and genital tract tissues of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 39 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…This increment is to compensate decreased platelets count previously mentioned in our results and confirmed by Aula et al . Moreover, Awaad added that the number and size of the splenic megakaryocytes were highly increased after magnetic NPs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This increment is to compensate decreased platelets count previously mentioned in our results and confirmed by Aula et al . Moreover, Awaad added that the number and size of the splenic megakaryocytes were highly increased after magnetic NPs.…”
Section: Discussionsupporting
confidence: 90%
“…Similar observations were reported by Mansouri et al on hepatocytes and Wang et al on splenocytes after ZnO NPs. Furthermore, other NPs like magnetite NPs were documented by Awaad to induce degeneration of splenocytes with multiple vacuoles and shrunken or condensed nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with Karabasz et al ( 83 ), who reported the safety and efficiency of nutrient delivery via organic nanocapsules. However, it is important to obtain detailed information and verify the safety of nanomaterials before use in human clinical trials ( 84 ).…”
Section: Biological Experimentsmentioning
confidence: 99%
“…Xu et al reported that Ti02 nanoparticles in mice caused a serious increase in the number of white blood cells [83]. Besides, iron oxide nanoparticles cause an increase in the number of white blood cells, and the liver and spleen are the most affected organs immunologically [84].…”
Section: Immune Systemmentioning
confidence: 99%